Acquirement of consumer perception on the ethicality and Islamicness of Islamic finance products and services - Musa, Muhammad Adli; Ahmad, Nadzrah (IIUM Press, International Islamic University Malaysia, 2018)
Islamic financial institutions (IFI) that are governed by sharī‘ah principles are expected to have inherently strong ethical roots such as promoting justice and avoiding any illegal and unethical elements. Hence, ethics has become a vital component in order to provide “value” for consumers. Indeed, there are numerous Qur’Énic injunctions and Prophetic traditions concerning ethical principles pertaining to Islamic finance, particularly those related to the ethics of business transactions. This research emphasises Islamic revealed guidance by compiling the Qur’Énic verses related to financial transactions using selected exegeses (tafasÊr). Furthermore, this research also focuses on how consumers perceive the ethicality of products and services offered by IFIs. It delineates the importance of ethical finance and the need for Islamic banking to align with ethical banking. Meanwhile, a quantitative research methodological approach was adopted in this study by utilising a structured questionnaire comprised of close-ended questions. The questionnaire was distributed among IIUM academic and administrative staff. The research findings show that the majority of respondents had a positive perception of the ethicality of Islamic finance products and services. This study also found that Islamic banking should formulate strategies to educate and offer unique products and services differentiated by underlying ethical values to increase its appeal to customers. The findings also suggest that ethics could be considered as a factor that encourages patronage of IFIs. Thus, this research is expected to assist IFIs to demonstrate their commitment and efforts in providing added value to customers.